Efficacy of Mikania micrantha Extract against Methicillin-resistant Staphylococcus aureus: A Mini Review - Baguingan, Shayne Aira B.; Jr., Romulo R. Macadangdang; Bermejo, Jovigail P.; Bondoc, Patricia E.; Cartina, Mary Louise L.; Liwa, Anjelo Nazarene S.; Quiambao, Beatrice Ann B.; Saldaña, Karla Joyce R.; Ugay, Dinalyn M.; Verano, Claudette Marie N. (Asian Journal of Biological and Life Sciences)
The development of antimicrobial resistance remains to be a major health concern imposing the need for new and effective antimicrobials. Methicillin-resistant Staphylococcus aureus (MRSA) is a multidrug-resistant bacteria showing resistance to common antibiotics (i.e. methicillin, penicillin, oxacillin, amoxicillin,). This mini-review sought to evaluate the proven antimicrobial properties of Mikania micrantha extract as stated by previous studies that will help us assess for the future studies. This is focused on summarizing the active metabolites and phytochemical compounds that can inhibit MRSA, the minimum inhibitory concentrations of the extract and its active compounds, and the challenges of using the extract as an antibacterial agent. The sources for the literature were ResearchGate, PubMed, ScienceDirect, and Google Scholar. A total of 30 out of 317 international literatures were included and published in English from 2011 and beyond. The results obtained presented the major phytochemical constituents and mechanism action of M. micrantha (i.e. sesquiterpene lactones, diterpenes, flavonoids, phenolic compounds). It holds probable antibacterial value against MRSA based on the reported MIC of the extract as a whole and its active compounds. The use of M. micrantha as an antibacterial agent is limited by its varying growth stability due to climatic factors, long lag period during its expansion, and the insolubility of its active constituents. In this regard, the state of M. micrantha is not at equilibrium which may directly affect the growth condition of the species thereby affecting its progression. Further evidence-based studies are still required to address the challenges encountered by previous studies in developing M. micrantha extract as an antimicrobial agent against MRSA.
Keywords: Antibiotic resistance; Antimicrobial property; Methicilin; Mikania micrantha; MRSA